Optimal Sizing of Photovoltaic Irrigation Water Pumping System in Samara - Ali H. Al-Hamdani; Majed Hassan; Roshen Tariq Ahmad (Engineering and Technology Journal, 2013)
Water pumping from wells and rivers for irrigation is a well established procedure on many farms in Iraq and is practical on various levels around the world. Typical irrigation systems consume a great amount of conventional energy through the use of electric motors and generators powered by fuel. The overall objective of this research was to determine the feasibility of using photovoltaic (PV) modules to power a water pump for a small-scale irrigation system in the North-West of Iraq (Samara). The study involved field observations, simulations of global solar radiation and PV electrical output. Field observations involved an installation of 24-monocrystaline silicon PV modules as shown in figure (1). This system was installed to give maximum power equal to (1960 watt) with maximum open circuit voltage (Voc = 175 volts) and maximum short circuit ( Isc= 14 Amp ). This module was connected to the pump via a charge controller and AC inverter. The parameters monitored were voltage, current, back-of-panel temperature, pressure, and flow. These observed parameters were used to determine PV electrical output and volume of water pumped. Site latitude, elevation, and panel tilt were applied to the solar radiation and PV electrical output models. PV electrical output and volume of water pumped were monitored between January 2000 and December 2000. As expected, an increase in power causes an increase in the volume of water pumped.